Mogroside ⅡE, an in vivo metabolite of sweet agent, alleviates acute lung injury via Pla2g2a-EGFR inhibition - Weichao Lü; Guoqing Ren; Kuniyoshi Shimizu; Renshi Li; Chaofeng Zhang (Food Science and Human Wellness)
In the face of increasingly serious environmental pollution, the health of human lung tissues is also facing serious threats. Mogroside ⅡE (M2E) is the main metabolite of sweetening agents mogrosides from the anti-tussive Chinese herbal Siraitia grosvenori. The study elucidated the anti-inflammatory action and molecular mechanism of M2E against acute lung injury (ALI). A lipopolysaccharide (LPS)-induced ALI model was established in mice and MH-S cells were employed to explore the protective mechanism of M2E through the western blotting, co-immunoprecipitation, and quantitative real time-PCR analysis. The results indicated that M2E alleviated LPS-induced lung injury through restraining the activation of secreted phospholipase A2 type IIA (Pla2g2a)-epidermal growth factor receptor (EGFR). The interaction of Pla2g2a and EGFR was identified by co-immunoprecipitation. In addition, M2E protected ALI induced with LPS against inflammatory and damage which were significantly dependent upon the downregulation of AKT and mTOR via the inhibition of Pla2g2a-EGFR. Pla2g2a may represent a potential target for M2E in the improvement of LPS-induced lung injury, which may represent a promising strategy to treat ALI.